Eculizumab as first line treatment for patients with severe presentation of Complement Factor H antibodies mediated Hemolytic Uremic Syndrome - Coccia, Paula Alejandra (2024)
Background:Complement Factor H (CFH) antibodies mediated Hemolytic Uremic Syndrome (HUS) has varying prevalence globally. Plasmapheresis and Immunosuppressive drugs are the standard treatment. Recently, Eculizumab has been reported as an effective alternative. The aim of this study is to report four children with CFH antibodies mediated HUS managed with Eculizumab plus immunosuppression as first line therapy.Methods:A retrospective chart review was conducted for children aged ≤ 18 years old with complement-mediated HUS in two referral centers. Patients with CFH antibodies mediated HUS treated with Eculizumab as first-line therapy were included.Results:Four children (aged 6–11 years old) were included. Dialysis was necessary in three patients. Eculizumab was administered 5–23 days after onset. None of them received plasmapheresis. Prednisone and mycophenolate mofetil were added after receiving positive CFH antibody results. Hematological signs and kidney function improved after the second Eculizumab dose. Eculizumab was discontinued in three patients after six months. One patient required rituximab due to persistent high CFH antibody titers, discontinuation of Eculizumab occurred after 15 months without recurrence. No treatment-related complications were observed. During a mean 12-month follow-up (range 6–24 months), no relapses were recorded and all patients ended with normal GFR.ConclusionOur data suggest that a short course of 6 months of C5 inhibitor might be sufficient to reverse TMA symptoms and improve kidney function in severe patients with CFH antibody mediated HUS. Simultaneously, adding immunosuppressive agents might reduce the risk of relapse and allow cessation of C5 inhibition in a shorter period of time.